Pain in Children With Developmental Disabilities: Development and Preliminary Effectiveness of a Pain Training Workshop for Respite Workers. Issue 5 (May 2018) - Genik, Lara M.; McMurtry, C. Meghan; Breau, Lynn M.; Lewis, Stephen P.; Freedman-Kalchman, Tamlyn
Abstract : Introduction: Pain in children with intellectual disabilities (ID) is common and complex, yet there is no standard pain training for their secondary caregivers (ie, respite staff). Objectives: Determine perceived pain training needs/preferences of children's respite staff (phase 1) and, use this information combined with extant research and guidelines to develop and pilot a training (phase 2). Methods: In phase 1, 22 participants responded to questionnaires and engaged in individual interviews/focus groups about their experiences with pain in children with ID, and perceived training needs/preferences. In phase 2, 50 participants completed knowledge measures and rated the feasibility of, and their own confidence and skill in, pain assessment and management for children with ID immediately before and after completing a pain training. They also completed a training evaluation. Results: Participants viewed pain training as beneficial. Their ideal training involved a half-day, multifaceted in-person program with a relatively small group of trainees incorporating a variety of learning activities, and an emphasis on active learning. Phase 2 results suggested that completion of the 3 to 3.5-hour pain training significantly increased respite workers' pain-related knowledge (effect sizes: r =0.81 to 0.88), as well as their ratings of the feasibility of, and their own confidence and skill in, pain assessment and management in children with ID (effect sizes: r =0.41 to 0.70). The training was rated favorably. Discussion: Training can positively impact respite workers' knowledge and perceptions about pain assessment and management. As such, they may be better equipped to care for children with ID in this area.